Drug-Induced Acute Pancreatitis and Pseudoaneurysms: An Ominous Combination - Branquinho,Diogo (2016)
Rupture of pseudoaneurysms is rare but can be life-threatening complications of acute or chronic pancreatitis, usually due to enzymatic digestion of vessel walls crossing peripancreatic fluid collections. We report the case of a 40 year-old female, with multisystemic lupus and anticoagulated for prior thrombotic events, admitted for probable cyclosporine-induced acute pancreatitis. Hemodynamic instability occurred due to abdominal hemorrhage from two pseudoaneurysms inside an acute peri-pancreatic collection. Selective angiography successfully embolized the gastroduodenal and pancreatoduodenal arteries. The hemorrhage recurred two weeks later and another successful embolization was performed and the patient remains well to date. The decision to restart anticoagulants and to suspend cyclosporine was challenging and required a multidisciplinary approach. Despite rare, bleeding from a pseudoaneurysm should be considered when facing a patient with pancreatitis and sudden signs of hemodynamic instability.